The effect of the intercellular adhesion molecule-1 and glycated haemoglobin on the management of diabetic neovascular glaucoma - Гузун, Ольга Володимирівна; Задорожний, Олег Сергійович; Величко, Людмила Миколаївна; Богданова, Олександра Вікторівна; Король, Андрій Ростиславович (My University, 2024)
Introduction: The study hypothesizes that some patients with diabetic neovascular glaucoma (NVG) do not fully respond to transscleral (TSC) cyclophotocoagulation (CPC) due to significant inflammation and insufficient glucose control. Objective: The study aimed to determine the effect of baseline blood levels of intercellular adhesion molecule-1 (ICAM-1) and glycated haemoglobin (HbA1c) on the management of patients with diabetic NVG by TSC CPC. Methods: This open prospective study included 70 diabetic patients (75 eyes; aged Ме 63.0 years) with painful NVG and 20 healthy individuals (aged Ме 61.5 years) as an immunological control. All patients underwent TSC СPC with a diode laser. Baseline HbA1c levels and ICAM-1 expression in blood samples were determined. Follow-up was 12 months. Results: One month after TSC CPC, IOP decreased by 28% compared to baseline. The effectiveness of laser treatment after 12 months of follow-up was 63% with IOP decrease by 46%. In patients with NVG, the initial level of ICAM-1 was 2.5 times higher than in the control group. Patients who did not fully respond to the first TSC CPC (30 eyes) and required additional laser procedure, had high initial HbA1c (9.5%) and high expression values of the ICAM-1 (609.0 cells/μL). Conclusions: Repeated procedures of TSC CPC at high IOP in diabetic patients with NVG are associated with high initial values of expression of ICAM-1 in peripheral blood and high HbA1c. The strategy of management of patients with diabetic NVG should be aimed at intensive glucose control and local anti-inflammatory treatment. Abbreviations: PDR = proliferative diabetic retinopathy, DR = diabetic retinopathy, NVG = neovascular glaucoma, TSC CPC = transscleral cyclophotocoagulation, ICAM-1 = intercellular adhesion molecule-1, HbA1c = glycated haemoglobin, IOP = intraocular pressure.
Keywords: glycated haemoglobin; intercellular adhesion molecule-1; neovascular glaucoma; proliferative diabetic retinopathy; transscleral cyclophotocoagulation